Development of Anti-Aging Nanoparticle Cosmetic Products Based on Young Coconut Fiber Waste (Cocos Nucifera) as an Effort to Utilize Sustainable Local Materials - Mokhamad Mahroji; Adi setiadi; Rini Setiawati; Febrina Nugrahini; Arif Hidayat (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
The development of natural-based anti-aging cosmetic products is an important innovation in the modern cosmetics industry, prioritizing safety, effectiveness, and environmental sustainability. Young coconut fiber (Cocos nucifera) waste contains bioactive compounds such as flavonoids, tannins, lignins, and natural antioxidants that have the potential to be used as active ingredients in anti-aging cosmetics. This study aims to analyze the development of nanoparticle-based anti-aging cosmetic products from young coconut fiber waste as an effort to utilize sustainable local materials. The research method uses a laboratory experimental approach with stages of active compound extraction, nanoparticle formulation, testing the physical characteristics of the preparation, and testing the antioxidant activity and product stability. Nanoparticle technology is applied to increase the penetration of active ingredients into the skin so that anti-aging effectiveness is more optimal. The results show that young coconut fiber waste extract has high antioxidant activity and can be formulated stably in the form of cosmetic nanoparticles. The resulting preparation has a homogeneous particle size, good spreadability, a pH that meets cosmetic standards, and optimal physical stability during storage. In addition, the use of young coconut fiber waste as a cosmetic raw material provides economic added value while supporting the concept of green cosmetics and reducing organic waste based on local resources. Thus, the development of nanoparticle anti-aging cosmetics based on young coconut fiber waste has the potential to become an innovation in natural cosmetic products that are effective, environmentally friendly, and competitive in the sustainable cosmetics industry.